97.9k views
0 votes
-6(6x - 1) +9=36x + 18

User DDay
by
5.6k points

2 Answers

3 votes
answer: 3

process:
distribute -6
-36x +6 + 9 = 36x + 18
add 36x to both sides canceling it out
find sun of like terms and you remain with 3!
User Antonio Vasilev
by
4.7k points
2 votes

Answer:

x = - 1 / 24

Explanation:

-6 ( 6x - 1 ) + 9 = 36x + 18

First, solve the brackets.

-36x + 6 + 9 = 36x + 18

Then, subtract 36x by both sides.

-36x - 36x + 6 + 9 = 18

-72x + 15 = 18

Now, Subtract 15 by both sides.

-72x = 18 - 15

-72x = 3

Now divide both sides -72 by both sides.

x = - 3 / 72

x = - 1 / 24

User Floriankrueger
by
4.7k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.